Emergence of Acinetobacter pittii Harboring New Delhi Metallo-β-Lactamase Genes in Daejeon, Korea - Sung, Ji Youn; Koo, Sun Hoe; Kim, Semi; Kwon, Gye Cheol (Annals of laboratory medicine, 2015)
Carbapenemase production has been reported worldwide in gram-negative bacteria, including Acinetobacter species. We detected carbapenemase-producing Acinetobacter pittii in clinical isolates in Daejeon, Korea. Twenty-one ertapenem-resistant A. pittii isolates screened with a disk diffusion method were characterized by using the Epsilon test, four multiplex PCR assays, and a multilocus sequence typing (MLST) scheme. A total of 21 A. pittii isolates harbored the metallo-β-lactamase (MBL) gene bla(IMP-1) or bla(NDM-1). Nineteen isolates containing bla(IMP-1) were resistant to imipenem and meropenem, but two isolates harboring bla(NDM-1) were susceptible to them. The sequence types (STs) of the two New Delhi MBL (NDM-1)-producing A. pittii isolates were ST70 and ST207, which differed from the STs (ST63, ST119, ST396, and a novel ST) of the IMP-1-producing A. pittii. This is the first report on NDM-1-producing A. pittii isolates in Korea. Our results emphasize that the study of NDM-1-producing gram-negative bacteria should involve carbapenem-susceptible as well as carbapenem-resistant isolates.